Genetic and Life Style Risk Factors for Recurrent Non-alcoholic Fatty Liver Disease Following Liver Transplantation - Iacob, Speranta; Beckebaum, Susanne; Iacob, Razvan; Gheorghe, Cristian; Cicinnati, Vito; Popescu, Irinel; Gheorghe, Liana (Frontiers in Nutrition, 2022)
Recurrent or de novo non-alcoholic fatty liver disease (NAFLD)/ non-alcoholic steatohepatitis (NASH) following liver transplantation (LT) is a frequent event being increasingly recognized over the last decade, but the impact of recurrent NASH on allograft and patient outcomes is not yet established. Taking into consideration the long term survival of liver transplanted patients and long term complications with associated morbidity and mortality, it is important to define and minimize risk factors for recurrent NAFLD/NASH. Metabolic syndrome, obesity, dyslipidemia, diabetes mellitus are life style risk factors that can be potentially modified by various interventions and thus, decrease the risk of recurrent NAFLD/NASH. On the other hand, genetic factors like recipient and/or donor PNPLA3, TM6SF2, GCKR, MBOAT7 or ADIPOQ gene polymorphisms proved to be risk factors for recurrent NASH. Personalized immunosuppression therapy in order to minimize the risks, as well as genetic screening of donors and recipients should be performed pre-LT in order to achieve an earlier diagnosis and treatment.